1994
DOI: 10.1007/bf02631326
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix and mouse mammary cell function: Comparison of substrata in culture

Abstract: Cultured mammary cells depend on interaction with a substratum for functional differentiation, even in the presence of lactogenic hormones. Protein synthesis and secretion by mouse mammary epithelial cells on floating collagen gels and (EHS) matrix were compared. Cells were prepared by collagenase digestion of tissue from mid-pregnant mice. Protein synthesis was consistently greater in cells attached to EHS matrix, and was associated with proportionately higher rates of protein secretion into culture medium. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
1
15
0
2
Order By: Relevance
“…Culture of mammary epithelial ceils on Matrigel, a reconstituted laminin-rich matrix extracted from the EHS tumor (Kleinman et al, 1986), has been shown to result in the formation of well organized, alveolar-like "mammospheres" (Barcellos-Hoff et al, 1989;Petersen et al, 1993;Hurley et al, 1994). To establish whether EpH4 subpopulations would differ in their ability to form three-dimensional structures on this substrate, ceils from each clone were seeded onto a thick layer of Matrigel and incubated for 10-15 d in complete medium.…”
Section: Resuufsmentioning
confidence: 99%
“…Culture of mammary epithelial ceils on Matrigel, a reconstituted laminin-rich matrix extracted from the EHS tumor (Kleinman et al, 1986), has been shown to result in the formation of well organized, alveolar-like "mammospheres" (Barcellos-Hoff et al, 1989;Petersen et al, 1993;Hurley et al, 1994). To establish whether EpH4 subpopulations would differ in their ability to form three-dimensional structures on this substrate, ceils from each clone were seeded onto a thick layer of Matrigel and incubated for 10-15 d in complete medium.…”
Section: Resuufsmentioning
confidence: 99%
“…This will lead to changes in the electrical potential of the mammary cells, which in turn will affect the activity of electrogenic transport systems. Mammary cells cultured on a reconstituted basement membrane do, however, form acinar structures enclosing a hollow lumen (Barcellos-Hoff et al 1989;Chen & Bissell, 1989;Hurley et al 1994;Blatchford et al 1995). These acini, termed mammospheres, appear to be polarized and are capable of secreting protein in a vectorial fashion (Blatchford et al 1995).…”
mentioning
confidence: 99%
“…The mechanisms underlying the changes in polarity are unclear; however, previous studies of 3D cultures of primary cells and established cell lines from mouse and human suggest that culturing stem/progenitor cells on substrata such as Matrigel™ (BD Biosciences) induces acinar structures with superior cell differentiation as defined by phenotype 4,12 (and as reviewed by Elliot and Yuan 8 ).…”
mentioning
confidence: 99%